Age and provenance constraints on seismically-determined crustal layers beneath the Paleozoic southern Central Asian Orogen, Inner Mongolia, China. (1st June 2016) - Jian, Ping; Kröner, Alfred; Shi, Yuruo; Zhang, Wei; Liu, Yaran; Windley, Brian F.; Jahn, Bor-ming; Zhang, Liqao; Liu, Dunyi
Highlights: Zircon ages explain the crustal composition of a seismic transect across Inner Mongolia. The middle crust comprises Proterozoic mafic and felsic gneisses. The lower crust forms a late Archaean granulite-facies assemblage. The deep crust of the southern CAOB and the northern NCC have a similar provenance. Abstract: We present 110 ages and 51 in-situ δ 18 O values for zircon xenocrysts from a post-99 Ma intraplate basaltic rock suite hosted in a subduction–accretion complex of the southern Central Asian Orogenic Belt in order to constrain a seismic profile across the Paleozoic Southern Orogen of Inner Mongolia and the northern margin of the North China Craton. Two zircon populations are recognized, namely a Phanerozoic group of 70 zircons comprising granitoid-derived (ca. 431–99 Ma; n = 31; peak at 256 Ma), meta-granitoid-derived (ca. 449–113 Ma; n = 24; peak at 251 Ma) and gabbro-derived (436–242 Ma; n = 15; peaks at 264 and 244 Ma) grains. Each textural type is characterized by a distinct zircon oxygen isotope composition and is thus endowed with a genetic connotation. The Precambrian population (2605–741 Ma; n = 40) exhibits a prominent age peak at 2520 Ma (granulite-facies metamorphism) and four small peaks at ca. 1900, 1600, and 800 Ma. Our new data, together with literature zircon ages, significantly constrain models of three seismically-determined deep crustal layers beneath the fossil subduction zone–forearc along the active northern margin of the North China Craton, namely: (1) an upper arc crust of early to mid-Paleozoic age, intruded by a major Permian–Triassic composite granitoid–gabbroic pluton (8–20 km depth); (2) a middle crust, predominantly consisting of mid-Meso- to Neoproterozoic felsic and mafic gneisses; and (3) a lower crust composed predominantly of late Archean granulite-facies rocks. We conclude that the Paleozoic orogenic crust is limited to the upper crustal level, and the middle to lower crust has a North China Craton affinity. Furthermore, integrating our data with surface geological, petrological and geochronological constraints, we present a new conceptual model of orogenic uplift, lithospheric delamination and crustal underthrusting for this key ocean–continent convergent margin.